Kritik Sosial Dalam Lirik Lagu (Analisis Wacana Lagu Maju Dari .Feast) - Tirta, Danu; Sari, Sapta; Dianthi, Martha Heriniazwi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Feast is a band that expresses social criticism through songs. Idealism in music, the use of words that contain figures of speech, and the themes presented make the author use the lyrics of the song "Maju" by the band .Feast as a study in this research. The method used in this research is qualitative method. The aim of this research is to find out the meaning of social criticism in the song "Maju" using Teun A. Van Dijk's approach. Critical discourse analysis using Teun A. van Dijk's approach model includes text dimensions, social cognition dimensions, and social context dimensions. The text dimension will analyze macro structure, superstructure and micro structure, then discuss it in the social cognition dimension and social context dimension to find the meaning of social criticism in the lyrics of the song "Maju". Analysis of song lyric data was carried out to describe the meaning of social criticism in the lyrics of the song "Maju" by .Feast. The results of this research show that there is social criticism in the lyrics of the song "Maju" sung by . survive and fight to the last drop of blood to defend the sovereignty of the Republic of Indonesia. Courage is something that must be instilled in every human being and defending the rights that belong to us is a must.